Core-shell nanostructures containing surface-bound zinc halides and zinc carboxylates
InP core-shell nanostructures with surface-bound zinc carboxylates and halides address lattice mismatch issues, enhancing quantum efficiency and stability, suitable for advanced display and lighting technologies.
Patent Information
- Application Number
- JP2022501284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-11
- Filing Date
- 2020-07-10
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-07-10
AI Technical Summary
Existing quantum dot light-emitting diodes (QLEDs) face challenges due to large core/shell lattice mismatch and lattice strain in InP-based nanostructures, leading to low hole mobility and quantum yield, which hinder their commercialization and performance.
Development of InP core-shell nanostructures with zinc carboxylates and zinc halides on the surface, specifically InP/ZnSe and Cd/ZnSe configurations, to minimize lattice mismatch and enhance stability and optical properties.
The InP core-shell nanostructures exhibit improved external quantum efficiency and stability, with quantum yields exceeding 80% and narrow emission spectra, making them suitable for advanced display and lighting applications.
Smart Images

Figure 0007616201000002 
Figure 0007616201000003 
Figure 0007616201000004
Abstract
Description
[Technical field]
[0001]
[0001] The present invention is in the field of nanostructure synthesis. Highly luminescent nanostructures are provided that are surface-treated with zinc acetate and zinc fluoride. Methods for producing nanostructures, films containing nanostructures, and devices containing nanostructures are also provided. [Background technology]
[0002]
[0002] ZnS is widely used as the shell material of QDs with Cd-based cores in quantum dot (QD) light-emitting diodes because the shell is stable, has good energy level alignment, and has a smaller degree of lattice mismatch between the core and the shell. In the past decade, device performance has been improved by changing the composition and thickness of the shell (e.g., Cd(core) / ZnS(shell)). Although the future looks promising, the commercialization of QLEDs containing cadmium QDs is severely restricted because cadmium is considered a hazardous material.
[0003]
[0003] Among potential alternatives to Cd-based II-VI compounds, InP QDs have been proposed as the most promising candidate for light-emitting applications due to their tunable band gap across the visible range and narrow spectral bandwidth.
[0004]
[0004] However, ZnS shells could not be adapted to InP cores due to the large core / shell lattice mismatch, large lattice distortion, excessively strong hole confinement in the InP core, and the deep HOMO level of the ZnS shell, as shown in Figure 1, which results in a high barrier for hole injection from the organic hole transport layer into the QDs and a low mobility of holes compared to electrons.
[0005]
[0005] In an attempt to minimize these drawbacks, ZnSe or gradient ZnSeS has been used as a buffer layer for the InP core and ZnS shell to minimize lattice mismatch and lattice distortion. However, the quantum yield (QY) of InP QDs is reduced when a thick ZnSe shell is used. This means that the lattice mismatch and lattice distortion cannot be minimized even when ZnSe or gradient ZnSeS is used as a buffer layer.
[0006] There is a need for core-shell nanostructure compositions that provide improved stability and improved optical properties when used to fabricate nanostructure films. Summary of the Invention
[0007]
[0007] Provided are InP core-shell nanostructure compositions that exhibit improved external quantum efficiency (EQE) and stability when used in devices. Also provided are core / shell nanostructures having zinc carboxylates and zinc halides bound to their surfaces.
[0008]
[0008] A population of nanostructures is provided that includes a nanocrystalline core and at least one shell having a zinc carboxylate and a zinc halide bound to a surface thereof. In some embodiments, the nanocrystalline core is selected from the group consisting of Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si 3 N 4 , Ge 3 N 4 , Al 2 O 3 , Al 2CO, and combinations thereof.
[0009] In some embodiments, the nanocrystalline core comprises InP. In some embodiments, the nanocrystalline core comprises CdSe.
[0010]
[0010] In some embodiments, at least one shell is ZnSe. In some embodiments, the thickness of at least one shell is about 1 nm. In some embodiments, the diameter of the nanostructure is about 4-12 nm.
[0011] In some embodiments, the nanostructure is an InP / ZnSe core-shell nanostructure.
[0012] In some embodiments, the nanostructures are Cd / ZnSe core-shell nanostructures.
[0013] In some embodiments, the nanostructures have an emission spectrum with a full width at half maximum (FWHM) of less than 40 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 38-39 nm.
[0014] In some embodiments, the quantum yield (QY%) of the nanostructions is greater than 80%. In some embodiments, the QY% of the nanostructures is 85-88%.
[0015]
[0015] In some embodiments, the zinc carboxylate is zinc acetate. In some embodiments, the zinc carboxylate is zinc acetate dihydrate. In some embodiments, the zinc halide is zinc fluoride.
[0016] A method of making a nanostructure as described herein comprising the steps of: (a) mixing the core-shell nanostructures in a solvent with a zinc carboxylate and a zinc halide under an inert atmosphere; (b) increasing the temperature of the mixture of (a) to a temperature between about 90° C. and about 350° C.; (c) isolating the core-shell nanocrystals having zinc acetate and zinc fluoride bound to their surfaces; Also provided is a method comprising:
[0017] In some embodiments, the solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, or dioctyl ether, or a combination thereof. In some embodiments, the solvent comprises 1-octadecene.
[0018]
[0018] In some embodiments, the temperature of the mixture in (a) is between about 0 °C and about 150 °C.
[0019] In some embodiments, the nanostructure is an InP / ZnSe core-shell nanostructure.
[0020]
[0020] In some embodiments, the zinc carboxylate is zinc acetate. In some embodiments, the zinc acetate is in the form of zinc acetate dihydrate.
[0021] In some embodiments, the InP / Se core / shell nanocrystals are (d) adding the InP cores to a solution containing a solvent, a ligand, and zinc chloride under an inert atmosphere at a temperature of about 80° C. to about 150° C.; (e) adding zinc bromide and gallium chloride to the solution obtained in (d); (f) adding a source of selenium to the solution obtained in (e); (g) heating the solution obtained in (f) to a temperature of about 150° C. to about 340° C.; (h) allowing the solution obtained in (g) to cool; is obtained by
[0022] In some embodiments, the solvent in (d) comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, or dioctyl ether, or a combination thereof. In some embodiments, the solvent in (d) comprises 1-octadecene.
[0023]
[0023] In some embodiments, the ligand is a fatty acid. In some embodiments, the fatty acid is lauric acid.
[0024] A nanostructured film comprising: (a) at least one population of nanostructures described herein; (b) at least one organic resin; Also provided is a nanostructure film comprising:
[0025] In some embodiments, the nanostructures are embedded in a matrix that forms a film.
[0026] 1. A nanostructured article comprising: (a) a first conductive layer; (b) a second conductive layer; (c) a nanostructure layer between the first conductive layer and the second conductive layer; wherein the nanostructure layer comprises a population of nanostructures as described herein.
[0027]
[0027] Also provided is a display device comprising the nanostructures described herein. In some embodiments, the display device comprises a film comprising the nanostructures. In some embodiments, the nanostructures are embedded in a matrix forming a film. In some embodiments, the film is disposed on a light guide plate.
[0028]
[0028] The accompanying drawings, which are incorporated into and constitute a part of this specification, illustrate the present invention and, together with the description, serve to further explain the principles of the present invention and enable those skilled in the art to make and use the invention. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a schematic illustrating the energy levels of CdSe-based QDs and InP / ZnSe / ZnS QDs, an organic hole-transporting layer (HTL), and an inorganic electron-transporting layer (ETL). [Diagram 2]
[0030] FIG. 1 is a schematic diagram illustrating the energy levels of HTL, CdSe / CdZnS QDs, InP / ZnSe / ZnS QDs, InP / ZnSe QDs, and surface-treated InP / ZnSe QDs. [Figure 3A]
[0031] Graphs showing current density versus voltage and luminance versus voltage for various QDs in the device. [Figure 3B]
[0032] 1 is a graph showing EQE versus luminance for various QDs in the device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030]
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The following definitions supplement the definitions in the art and are directed to this application, and are not attributable to any related or unrelated cases, such as any commonly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be used to carry out the tests, the preferred materials and methods are described herein. Therefore, the terminology used herein is for the purpose of describing specific embodiments only and is not intended to be limiting.
[0031]
[0034] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and so forth.
[0032]
[0035] As used herein, the term "about" indicates that the numerical value of a given quantity varies by ±10% relative to that numerical value. For example, "about 100 nm" encompasses a size range from 90 nm to 110 nm, inclusive.
[0033]
[0036] A "nanostructure" is a structure having at least one region or characteristic dimension with a dimension less than about 500 nm. In some embodiments, the dimension of a nanostructure is less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. Typically, the region or characteristic dimension will be along the shortest axis of the structure. Examples of such structures include nanowires, nanorods, nanotubes, branched nanostructures, nanotetrapods, tripods, bipods, nanocrystals, nanodots, quantum dots, nanoparticles, and the like. Nanostructures can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or combinations thereof. In some embodiments, each of the three dimensions of a nanostructure is less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.
[0034]
[0037] The term "heterostructure" as used in reference to nanostructures refers to a nanostructure that features at least two different and / or distinguishable types of material. Typically, one region of the nanostructure includes a first type of material, while a second region of the nanostructure includes a second type of material. In certain embodiments, the nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material, with the different types of materials being distributed radially, e.g., along the long axis of a nanowire, along the long axis of an arm of a branched nanowire, or along the center of a nanocrystal. The shell may, but need not, completely cover the adjacent material to be considered a shell or for the nanostructure to be considered a heterostructure; for example, a nanocrystal characterized by a core of one material surrounded by small islands of a second material is a heterostructure. In other embodiments, the different types of materials are distributed at different locations within the nanostructure; e.g., along the major (long) axis of a nanowire, or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure may comprise entirely different materials, or the different regions may comprise a base material (e.g., silicon) that contains different dopants or the same dopant at different concentrations.
[0035]
[0038] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section perpendicular to a first axis of the nanostructure, the first axis being the largest difference in length relative to the second and third axes (the second and third axes being most nearly equal in length to each other). The first axis is not necessarily the longest axis of the nanostructure; for example, in the case of a disk-shaped nanostructure, the cross section would be a substantially circular cross section perpendicular to the short longitudinal axis of the disk. If the cross section is not circular, the diameter is the average of the long and short axes of the cross section. For elongated or high aspect ratio nanostructures, such as nanowires, the diameter is measured in a cross section perpendicular to the longest axis of the nanowire. For spherical nanostructures, the diameter is measured from one side to the other through the center of the sphere.
[0036]
[0039] The terms "crystalline" or "substantially crystalline", when used in relation to nanostructures, generally refer to the nanostructure exhibiting long-range order across one or more dimensions of the structure. As single-crystal order cannot exist beyond the boundaries of the crystal, one skilled in the art will appreciate that the term "long-range order" will depend on the absolute size of a particular nanostructure. In this case, "long-range order" will refer to substantial order across at least most of the dimensions of the nanostructure. In some instances, the nanostructure may have an oxide or other coating, or may be comprised of a core and at least one shell. In such instances, it will be understood that the oxide, shell, or other coating may exhibit such order, but need not do so (e.g., may be amorphous, polycrystalline, or otherwise). In such instances, the phrases "crystalline", "substantially crystalline", "substantially monocrystalline", or "monocrystalline" refer to the central core of the nanostructure (excluding any coating layers or shells). As used herein, "crystalline" or "substantially crystalline" is intended to encompass structures that contain various defects, stacking disorders, atomic substitutions, and the like, so long as the structures exhibit substantial long-range order (e.g., order over at least about 80% of the length of at least one axis of the nanostructure or its core). Furthermore, it will be understood that the interface between the core and the outer surface of the nanostructure, or the interface between the core and an adjacent shell, or the interface between a shell and an adjacent second shell, may include non-crystalline regions or may even be amorphous. This does not prevent a nanostructure from having crystallinity or substantially crystallinity as defined herein.
[0037]
[0040] The term "monocrystalline" when used in reference to a nanostructure indicates that the nanostructure is substantially crystalline and comprises substantially a single crystal. When used in reference to a nanostructure heterostructure comprising a core and one or more shells, "monocrystalline" indicates that the core is substantially crystalline and comprises substantially a single crystal.
[0038]
[0041] A "nanocrystal" is a nanostructure that is substantially monocrystalline. Thus, a nanocrystal has at least one region or characteristic dimension that has a dimension less than about 500 nm. In some embodiments, the dimensions of a nanocrystal are less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. The term "nanocrystal" is intended to encompass substantially monocrystalline nanostructures that contain defects, stacking imperfections, atomic substitutions, and the like, as well as substantially monocrystalline nanostructures that are free of such defects, imperfections, or substitutions. In the case of nanocrystal heterostructures that comprise a core and one or more shells, the core of the nanocrystal is usually substantially monocrystalline, but the shells need not be. In some embodiments, the three dimensions of the nanocrystal are each less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.
[0039]
[0042] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum or exciton confinement. Quantum dots can be substantially homogeneous in material properties or, in certain embodiments, can be heterogeneous, e.g., comprising a core and at least one shell. The optical properties of quantum dots can be influenced by their particle size, chemical composition, and / or surface composition, and can be measured by suitable optical tests available in the art. If the size of the nanocrystals can be tailored, e.g., in the range of about 1 nm to about 15 nm, it becomes possible to cover the entire range of the optical spectrum in photoemission, enabling a wide variety of color renderings.
[0040]
[0043] A "ligand" is a molecule that can interact (weakly or strongly) with one or more facets of a nanostructure, for example, via covalent, ionic, van der Waals, or other molecular interactions with the surface of the nanostructure.
[0041]
[0044] "Photoluminescence quantum yield" (PLQY), for example, is the ratio of photons emitted to photons absorbed by a nanostructure or population of nanostructures. As is known in the art, quantum yield is usually determined by comparative methods using well-characterized reference samples with known quantum yield values.
[0042]
[0045] "Peak emission wavelength" (PWL) is the wavelength at which the radiometric emission spectrum of a light source reaches a maximum value.
[0043]
[0046] The term "shell" as used herein refers to material deposited on a core or on a previously deposited shell of the same or different composition, resulting from a single act of depositing the shell material. The exact thickness of the shell depends on the material as well as the precursor input and conversion, and can be reported in nanometers or monolayers. As used herein, "target shell thickness" refers to the intended shell thickness used to calculate the amount of precursor required. As used herein, "actual shell thickness" refers to the amount of shell material actually deposited after synthesis, which can be measured by methods known in the art. By way of example, the actual shell thickness can be measured by comparing the particle diameters determined from transmission electron microscopy (TEM) images of the nanocrystals before and after shell synthesis.
[0044]
[0047] The term "full width at half maximum" (FWHM) as used herein is a measure of the size distribution of nanoparticles. The emission spectrum of nanoparticles generally has a Gaussian curve shape. The width of the Gaussian curve is defined as the FWHM and gives an insight into the size distribution. A smaller FWHM corresponds to a narrower size distribution of quantum dot nanocrystals. The FWHM also depends on the peak emission wavelength.
[0045]
[0048] The term "half width at half maximum" (HWHM) as used herein is a measure of the particle size distribution of nanoparticles estimated from the UV-Vis spectroscopic curve. The HWHM of the first exciton absorption peak on the low energy side can be used as a suitable indicator of the particle size distribution, with smaller HWHM values corresponding to narrower particle size distribution.
[0046] Nanostructure Composition
[0049] In some embodiments, the present disclosure provides nanostructure compositions comprising core-shell nanostructures surface treated with zinc acetate and zinc fluoride.
[0047]
[0050] In some embodiments, the present disclosure provides a nanostructure composition comprising an InP / ZnSe core-shell nanostructure, hi some embodiments, the ZnSe shell has a thickness between about 0.01 nm and about 5 nm.
[0048]
[0051] In some embodiments, the nanostructures are quantum dots.
[0049] Nanostructure Core
[0052] Quantum dots (or other nanostructures) for use in the present invention can be made from any suitable material, preferably inorganic materials, more preferably inorganic conductive or semiconducting materials. Suitable semiconducting materials include any type of semiconductor, including Group II-VI, Group III-V, Group IV-VI, and Group IV semiconductors. Suitable semiconductor materials include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3 N 4 , Ge 3 N 4 , Al 2 O 3 , Al 2 CO, and combinations thereof.
[0050]
[0053] The synthesis of Group II-VI nanostructures has been described in U.S. Patent No. 6,225,198, U.S. Patent No. 6,322,901, U.S. Patent No. 6,207,229, U.S. Patent No. 6,607,829, U.S. Patent No. 6,861,155, U.S. Patent No. 7,060,243, U.S. Patent No. 7,125,605, U.S. Patent No. 7,374,824, U.S. Patent No. 7,566,476, U.S. Patent No. 8,101,234, and U.S. Patent No. 8,158,193, as well as U.S. Patent Application Publication No. 2011 / 0262752 and U.S. Patent Application Publication No. 2011 / 0263062. In some embodiments, the core is a Group II-VI nanocrystal selected from the group consisting of ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgSe, HgS, and HgTe, hi some embodiments, the core is a nanocrystal selected from the group consisting of ZnSe, ZnS, CdSe, and CdS.
[0051]
[0054] Although II-VI nanostructures such as CdSe and CdS quantum dots can exhibit desirable luminescence behavior, the toxicity of cadmium limits the applications in which such nanostructures can be used. Therefore, less toxic alternatives with favorable luminescence properties are highly desirable. In general, III-V nanostructures, and in particular InP-based nanostructures, are the best alternatives among known cadmium-based materials due to their consistent emission range.
[0052]
[0055] The synthesis of InP-based nanostructures is described, for example, in Xie, R., et al., “Colloidal InP nanocrystals as efficient emitters covering blue to near-infrared,” J. Am. Chem. Soc. 129:15432-15433 (2007); Micic, O. I., et al., “Core-shell quantum dots of lattice-matched ZnCdSe2 shells on InP cores: Experiment and theory,” J. Phys. Chem. B 104:12149-12156 (2000); Liu, Z., et al., “Coreduction colloidal synthesis of III-V nanocrystals: The case of InP,” Angew. Chem. Int. Ed. Engl. 47:3540-3542 (2008); Li, L., et al., “Economic synthesis of high quality InP nanocrystals using calcium phosphide as the phosphorus precursor,” Chem. Mater. 20:2621-2623 (2008); D. Battaglia and X. Peng, “Formation of high quality InP and InAs nanocrystals in a noncoordinating solvent,” Nano Letters 2:1027-1030 (2002); Kim, S., et al., “Highly luminescent InP / GaP / ZnS nanocrystals and their application to white light-emitting diodes,” J. Am. Chem. Soc. 134:3804-3809 (2012); Nann, T., et al., “Water splitting by visible light: A nanophotocathode for hydrogen production,” Angew. Chem. Int. Ed.49:1574-1577(2010);Borchert,H.,et al.,“Investigation of ZnS passivated InP nanocrystals by XPS,”Nano Letters 2:151-154(2002);L.Li and P.Reiss,“One-pot synthesis of highly luminescent InP / ZnS nanocrystals without precursor injection,”J.Am.Chem.Soc.130:11588-11589(2008);Hussain,S.,et al.“One-pot fabrication of high-quality InP / ZnS(core / shell)quantum dots and their application to cellular imaging,”Chemphyschem.10:1466-1470 (2009);Xu,S.,et al.,“Rapid synthesis of high-quality InP nanocrystals,”J.Am.Chem.Soc.128:1054-1055(2006);Micic,O.I.,et al.,“Size-dependent spectroscopy of InP quantum dots,”J.Phys.Chem.B 101:4904-4912(1997);Haubold,S.,et al.,“Strongly luminescent InP / ZnS core-shell nanoparticles,”Chemphyschem.5:331-334(2001);CrosGagneux,A.,et al.,“Surface chemistry of InP quantum dots:A comprehensive study,”J.Am.Chem.Soc.132:18147-18157(2010);Micic,O.I.,et al.,“Synthesis and characterization of InP,GaP,and GalnP2 quantum dots,”J. Phys.Chem.99:7754-7759(1995);Guzelian,A.A.,et al.,“Synthesis of size-selected,surface-passivated InP nanocrystals,”J. Phys.Chem.100:7212-7219(1996);Lucey,DW,et al.,“Monodispersed InP quantum dots prepared by colloidal chemistry in a non-coordinating solvent,” Chem.Mater.17:3754-3762(2005);Lim,J.,et al.,“InP@ZnSeS,core@composition gradient shell quantum dots with enhanced stability,”Chem.Mater.23:4459-4463(2011);andZan,F.,et al.,“Experimental studies on blinking behavior of single InP / ZnS quantum dots:Effects of synthetic conditions and UV irradiation,”J.Phys.Chem.C 116:394-3950 (2012). However, these efforts have only achieved limited success in producing InP nanostructures with high quantum yields.
[0053]
[0056] In some embodiments, the InP core is doped. In some embodiments, the dopant of the nanocrystalline core comprises a metal, such as one or more transition metals. In some embodiments, the dopant is a transition metal selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, and combinations thereof. In some embodiments, the dopant comprises a non-metal. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS 2 , CuInSe 2, AlN, AlP, AlAs, GaN, GaP, or GaAs.
[0054]
[0057] In some embodiments, the cores are purified prior to depositing the shell, hi some embodiments, the cores are filtered to remove precipitates from the core solution.
[0055]
[0058] In some embodiments, the diameter of the InP core is determined using quantum confinement. Quantum confinement in zero-dimensional nanocrystals, such as quantum dots, arises from spatial confinement of electrons to crystallite boundaries. Quantum confinement can be observed when the diameter of the material is on the order of the de Broglie wavelength in the wave function. The electronic and optical properties of nanoparticles deviate substantially from those of bulk materials. The particle behaves as if it were free when the confinement length is longer than the particle's wavelength. While in this state, the band gap remains at its original energy because there is a continuum of energy states. However, as the confinement length decreases and reaches a certain limit, usually the nanoscale, the energy spectrum becomes discrete. As a result, the band gap becomes size dependent.
[0056]
[0059] In some embodiments, the nanostructures are free from cadmium. The term "cadmium-free" as used herein means that the nanostructures contain less than 100 ppm cadmium by weight. The Restriction of Hazardous Substances (RoHS) compliance definition requires that raw homogeneous precursor materials do not contain more than 0.01% (100 ppm) cadmium by weight. The amount of cadmium in the Cd-free nanostructures of the present invention is limited by the trace metal concentration in the precursor materials. The trace metal (including cadmium) concentration in the precursor materials of the Cd-free nanostructures can be measured by inductively coupled plasma mass spectrometry (ICP-MS) analysis and is at the parts per billion (ppb) level. In some embodiments, a "cadmium-free" "nanostructure" contains less than about 50 ppm, less than about 20 ppm, less than about 10 ppm, or less than about 1 ppm cadmium.
[0057] shell
[0060] Exemplary materials for making the shell include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si 3 N 4 , Ge 3 N 4 , Al 2 O 3 , Al 2 CO, and combinations thereof.
[0058]
[0061] In some embodiments, the shell is a mixture of at least two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of three of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is a mixture of zinc and sulfur; zinc and selenium; zinc, sulfur, and selenium; zinc and tellurium; zinc, tellurium, and sulfur; zinc, tellurium, and selenium; zinc, cadmium, and sulfur; zinc, cadmium, and selenium; cadmium and sulfur; cadmium and selenium; cadmium and zinc; cadmium, zinc, and sulfur; cadmium, selenium, and sulfur; cadmium and zinc; cadmium, zinc, and selenium; or a mixture of cadmium, zinc, sulfur, and selenium. In some embodiments, the shell is a mixture of zinc and selenium, hi some embodiments, the shell is a mixture of zinc and sulfur.
[0059]
[0062] Exemplary core / shell luminescent nanostructures include, but are not limited to, CdSe / ZnSe and InP / ZnSe (represented as core / shell).
[0060]
[0063] In some embodiments, the shell comprises ZnSe. The thickness of the shell can be adjusted by varying the amount of precursors provided. To obtain a given shell thickness, at least one of the precursors is optionally provided in an amount that results in a shell of a predetermined thickness after the growth reaction is substantially complete. In some embodiments, the molar ratio of the zinc source to the selenium source is from about 0.01:1 to about 1:1.5, from about 0.01:1 to about 1:1.25, from about 0.01:1 to about 1:1, from about 0.01:1 to about 1:0.75, from about 0.01:1 to about 1:0.5, from about 0.01:1 to about 1:0.25, from about 0.01:1 to about 1:0.05, from about 0.05:1 to about 1:1.5, from about 0.05:1 to about 1:1.25, from about 0.05:1 to about 1:1, from about 0.05:1 to about 1:0.75, from about 0.05:1 to about 1:0.5, from about 0.05:1 to about 1:0.2 5, about 0.25:1 to about 1:1.5, about 0.25:1 to about 1:1.25, about 0.25:1 to about 1:1, about 0.25:1 to about 1:0.75, about 0.25:1 to about 1:0.5, about 0.5:1 to about 1:1.5, about 0.5:1 to about 1:1.25, about 0.5:1 to about 1:1, about 0.5:1 to about 1:0.75, about 0.75:1 to about 1:1.5, about 0.75:1 to about 1:1.25, about 0.75:1 to about 1:1, about 1:1 to about 1:1.5, about 1:1 to about 1:1.25, or about 1:1.25 to about 1:1.5.
[0061]
[0064] The thickness of the ZnSe shell layer can be adjusted by varying the amount of zinc and selenium sources provided and / or by using longer reaction times and / or higher temperatures, with at least one of the sources optionally provided in an amount to obtain a layer of a predetermined thickness once the growth reaction is substantially complete.
[0062]
[0065] The thickness of the ZnSe thin shell can be measured by techniques known to those skilled in the art. In some embodiments, the thickness of the inner thin shell can be determined by comparing the average diameter of the nanostructure before and after adding the inner thin shell. In some embodiments, the average diameter of the nanostructure before and after adding the inner thin shell can be measured by TEM. In some embodiments, the thickness of the ZnSe shell is about 0.01 nm to about 0.35 nm, about 0.01 nm to about 0.3 nm, about 0.01 nm to about 0.25 nm, about 0.01 nm to about 0.2 nm, about 0.01 nm to about 0.1 nm, about 0.01 nm to about 0.05 nm, about 0.05 nm to about 0.35 nm, about 0.05 nm to about 0.3 nm, about 0.05 nm to about 0.25 nm, about 0.05 nm to about 0. 0.2 nm, about 0.05 nm to about 0.1 nm, about 0.1 nm to about 0.35 nm, about 0.1 nm to about 0.3 nm, about 0.1 nm to about 0.25 nm, about 0.1 nm to about 0.2 nm, about 0.2 nm to about 0.35 nm, about 0.2 nm to about 0.3 nm, about 0.2 nm to about 0.25 nm, about 0.25 nm to about 0.35 nm, about 0.25 nm to about 0.3 nm, or about 0.3 nm to about 0.35 nm.
[0063]
[0066] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.
[0064]
[0067] In some embodiments, the selenium source is an alkyl-substituted selenide urea. In some embodiments, the selenium source is a phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenide urea, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, or tri(tert-butyl)phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.
[0065]
[0068] In some embodiments, the ZnSe shell is synthesized in the presence of at least one nanostructure ligand. The ligand can, for example, increase the miscibility of the nanostructure in a solvent or polymer (allowing the nanostructure to be distributed throughout the composition so that the nanostructure does not aggregate), increase the quantum yield of the nanostructure, and / or preserve the emission of the nanostructure (e.g., when the nanostructure is incorporated into a matrix). In some embodiments, the ligands for the InP core synthesis and the shell synthesis are the same. In some embodiments, the ligands for the core synthesis and the shell synthesis are different. After synthesis, any ligands present on the nanostructure surface can be exchanged for different ligands with other desirable properties. Exemplary ligands are disclosed in U.S. Pat. No. 7,572,395, U.S. Pat. No. 8,143,703, U.S. Pat. No. 8,425,803, U.S. Pat. No. 8,563,133, U.S. Pat. No. 8,916,064, U.S. Pat. No. 9,005,480, U.S. Pat. No. 9,139,770, and U.S. Pat. No. 9,169,435, and U.S. Patent Application Publication No. 2008 / 0118755.
[0066]
[0069] Ligands suitable for the synthesis of the shell are known to those skilled in the art. In some embodiments, the ligand is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is oleic acid.
[0067] Fabrication of InP cores with ZnSe shells - Method A
[0070] In some embodiments, the present invention provides a method for fabricating a core / shell InP / ZnSe nanostructure, comprising: (a) mixing an In source, a P source, a zinc source, and a selenium source; (b) increasing the temperature of the mixture of (a) to a temperature between about 200° C. and about 350° C.; thereby obtaining a nanostructure.
[0068]
[0071] In some embodiments, the core / shell nanostructures are prepared in the presence of a solvent. In some embodiments, the solvent is selected from the group consisting of 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, and dioctyl ether. In some embodiments, the solvent is 1-octadecene.
[0069]
[0072] In some embodiments, the core and shell precursors are mixed in (a) at a temperature between about 0° C. and about 150° C., about 0° C. and about 100° C., about 0° C. and about 50° C., about 0° C. and about 30° C., about 0° C. and about 20° C., about 20° C. and about 150° C., about 20° C. and about 100° C., about 20° C. and about 50° C., about 20° C. and about 30° C., about 30° C. and about 150° C., about 30° C. and about 100° C., about 30° C. and about 50° C., about 50° C. and about 150° C., about 50° C. and about 100° C., or about 100° C. and about 150° C. In some embodiments, the core and shell precursors are mixed in (a) at a temperature between about 20° C. and about 30° C.
[0070]
[0073] In some embodiments, the zinc source is zinc chloride.
[0071]
[0074] In some embodiments, the selenium source is selenium powder.
[0072]
[0075] In some embodiments, the temperature of the mixture in (b) is raised to a temperature between about 200° C. to about 350° C., about 200° C. to about 310° C., about 200° C. to about 280° C., about 200° C. to about 250° C., about 200° C. to about 225° C., about 225° C. to about 350° C., about 225° C. to about 310° C., about 225° C. to about 280° C., about 225° C. to about 250° C., about 250° C. to about 350° C., about 250° C. to about 310° C., about 250° C. to about 280° C., about 280° C. to about 350° C., about 280° C. to about 310° C., or about 310° C. to about 350° C. In some embodiments, the temperature of the mixture in (b) is raised to a temperature between about 280° C. to about 310° C.
[0073]
[0076] In some embodiments, in (b), the time for reaching the high temperature is from about 2 minutes to about 240 minutes, from about 2 minutes to about 200 minutes, from about 2 minutes to about 100 minutes, from about 2 minutes to about 60 minutes, from about 2 minutes to about 40 minutes, from about 5 minutes to about 240 minutes, from about 5 minutes to about 200 minutes, from about 5 minutes to about 100 minutes, from about 5 minutes to about 60 minutes, from about 5 minutes to about 40 minutes, from about 10 minutes to about 240 minutes, from about 10 minutes to about 200 minutes, the reaction time is between about 10 minutes and about 100 minutes, about 10 minutes and about 60 minutes, about 10 minutes and about 40 minutes, about 40 minutes and about 240 minutes, about 40 minutes and about 200 minutes, about 40 minutes and about 100 minutes, about 40 minutes and about 60 minutes, about 60 minutes and about 240 minutes, about 60 minutes and about 200 minutes, about 60 minutes and about 100 minutes, about 100 minutes and about 240 minutes, about 100 minutes and about 200 minutes, or about 200 minutes and about 240 minutes.
[0074]
[0077] In some embodiments, after the elevated temperature is reached in (b), the temperature is maintained for a time period between about 1 minute and about 240 minutes, between about 1 minute and about 90 minutes, between about 1 minute and about 60 minutes, between about 1 minute and about 30 minutes, between about 1 minute and about 15 minutes, between about 1 minute and about 5 minutes, between about 5 minutes and about 240 minutes, between about 5 minutes and about 90 minutes, between about 5 minutes and about 60 minutes, between about 5 minutes and about 30 minutes, between about 5 minutes and about 15 minutes, between about 15 minutes and about 240 minutes, between about 15 minutes and about 90 minutes, between about 15 minutes and about 60 minutes, between about 15 minutes and about 30 minutes, between about 30 minutes and about 240 minutes, between about 30 minutes and about 90 minutes, between about 30 minutes and about 60 minutes, between about 60 minutes and about 240 minutes, between about 60 minutes and about 90 minutes, or between about 90 minutes and about 240 minutes.
[0075]
[0078] In some embodiments, the progress of the reaction is monitored by testing a sample from the mixture or by monitoring the mixture in situ using UV-visible spectroscopy. In some embodiments, once the mixture reaches an elevated temperature in (b), the temperature is monitored until the peak absorbance by UV-visible spectroscopy of the mixture reaches a value between about 350 nm and about 500 nm, between about 350 nm and about 475 nm, between about 350 nm and about 450 nm, between about 350 nm and about 425 nm, between about 350 nm and about 400 nm, between about 350 nm and about 375 nm, between about 375 nm and about 500 nm, between about 375 nm and about 475 ... 5 nm to about 450 nm, about 375 nm to about 425 nm, about 375 nm to about 400 nm, about 400 nm to about 500 nm, about 400 nm to about 475 nm, about 400 nm to about 450 nm, about 400 nm to about 425 nm, about 425 nm to about 475 nm, about 425 nm to about 450 nm, about 450 nm to about 500 nm, about 450 nm to about 475 nm, or about 475 nm to about 500 nm. In some embodiments, once the mixture has reached an elevated temperature in (b), this temperature is maintained until a sample taken from the mixture has a peak absorbance by UV-visible spectroscopy between about 425 nm and about 450 nm.
[0076]
[0079] In some embodiments, additional shells are produced by adding shell material precursors to the reaction mixture and then maintaining the mixture at an elevated temperature. Typically, additional shell precursors are provided once the reaction of the previous shell is substantially complete (e.g., once at least one of the previous precursors has been depleted or removed from the reaction or no further growth is detected). This addition of additional precursors produces additional shells.
[0077]
[0080] In some embodiments, the nanostructures are cooled before adding additional shell material precursor to impart an additional shell, hi some embodiments, the nanostructures are maintained at an elevated temperature before adding shell material precursor to impart an additional shell.
[0078] Fabrication of InP / ZnSe core-shell nanostructures - Method B
[0081] In some embodiments, the present invention provides a method for fabricating a core / shell InP / ZnSe nanostructure, comprising: (a) combining a zinc or selenium shell precursor and a solvent; (b) raising, lowering, or maintaining the temperature of the mixture of (a) at a temperature between about 50° C. and about 250° C.; (c) adding InP core and zinc or selenium shell precursors to the mixture of (b); thereby obtaining an InP / ZnSe nanostructure.
[0079]
[0082] In some embodiments, the core / shell nanostructures are prepared in the presence of a solvent. In some embodiments, the solvent is selected from the group consisting of 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, and dioctyl ether. In some embodiments, the solvent is 1-octadecene.
[0080]
[0083] In some embodiments, the zinc / selenium shell precursor and the solvent are mixed in (a) at a temperature between about 0° C. and about 150° C., about 0° C. and about 100° C., about 0° C. and about 50° C., about 0° C. and about 30° C., about 0° C. and about 20° C., about 20° C. and about 150° C., about 20° C. and about 100° C., about 20° C. and about 50° C., about 20° C. and about 30° C., about 30° C. and about 150° C., about 30° C. and about 100° C., about 30° C. and about 50° C., about 50° C. and about 150° C., about 50° C. and about 100° C., or about 100° C. and about 150° C. In some embodiments, the zinc / selenium shell source and the solvent are mixed in (a) at a temperature between about 20° C. and about 30° C.
[0081]
[0084] In some embodiments, the mixture in (a) further comprises at least one ligand for the nanostructure. The ligand can, for example, increase the miscibility of the nanostructure in a solvent or polymer (allowing the nanostructure to be distributed throughout the composition so that the nanostructure does not aggregate), increase the quantum yield of the nanostructure, and / or preserve the emission of the nanostructure (e.g., when the nanostructure is incorporated into a matrix). In some embodiments, the ligands for the core synthesis and the shell synthesis are the same. In some embodiments, the ligands for the core synthesis and the shell synthesis are different. After synthesis, any ligands present on the nanostructure surface can be exchanged for different ligands having other desirable properties. Exemplary ligands are disclosed in U.S. Pat. No. 7,572,395, U.S. Pat. No. 8,143,703, U.S. Pat. No. 8,425,803, U.S. Pat. No. 8,563,133, U.S. Pat. No. 8,916,064, U.S. Pat. No. 9,005,480, U.S. Pat. No. 9,139,770, and U.S. Pat. No. 9,169,435, and U.S. Patent Application Publication No. 2008 / 0118755.
[0082]
[0085] In some embodiments, the ligand mixed with the first shell precursor and the solvent in (a) is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is lauric acid.
[0083]
[0086] In some embodiments, in (b), the temperature of the mixture is from about 50° C. to about 250° C., from about 50° C. to about 200° C., from about 50° C. to about 150° C., from about 50° C. to about 125° C., from about 50° C. to about 100° C., from about 50° C. to about 75° C., from about 75° C. to about 250° C., from about 75° C. to about 200° C., from about 75° C. to about 150° C., from about 75° C. to about 125° C., from about 75° C. to about The temperature is increased, decreased, or maintained at a temperature between about 100° C., about 100° C. to about 250° C., about 100° C. to about 200° C., about 100° C. to about 150° C., about 100° C. to about 125° C., about 125° C. to about 250° C., about 125° C. to about 200° C., about 125° C. to about 150° C., about 150° C. to about 250° C., about 150° C. to about 200° C., or about 200° C. to about 250° C. In some embodiments, in (b), the temperature of the mixture is increased, decreased, or maintained at a temperature between about 50° C. to about 150° C.
[0084]
[0087] In some embodiments, in (b), the time to reach this temperature is about 2 minutes to about 240 minutes, about 2 minutes to about 200 minutes, about 2 minutes to about 100 minutes, about 2 minutes to about 60 minutes, about 2 minutes to about 40 minutes, about 5 minutes to about 240 minutes, about 5 minutes to about 200 minutes, about 5 minutes to about 100 minutes, about 5 minutes to about 60 minutes, about 5 minutes to about 40 minutes, about 10 minutes to about 240 minutes, about 10 minutes to about 200 minutes. the reaction time is between about 10 minutes and about 100 minutes, about 10 minutes and about 60 minutes, about 10 minutes and about 40 minutes, about 40 minutes and about 240 minutes, about 40 minutes and about 200 minutes, about 40 minutes and about 100 minutes, about 40 minutes and about 60 minutes, about 60 minutes and about 240 minutes, about 60 minutes and about 200 minutes, about 60 minutes and about 100 minutes, about 100 minutes and about 240 minutes, about 100 minutes and about 200 minutes, or about 200 minutes and about 240 minutes.
[0085]
[0088] In some embodiments, the temperature of the mixture in (c) is from about 50° C. to about 250° C., from about 50° C. to about 200° C., from about 50° C. to about 150° C., from about 50° C. to about 125° C., from about 50° C. to about 100° C., from about 50° C. to about 75° C., from about 75° C. to about 250° C., from about 75° C. to about 200° C., from about 75° C. to about 150° C., from about 75° C. to about 125° C., The temperature is between about 75° C. to about 100° C., about 100° C. to about 250° C., about 100° C. to about 200° C., about 100° C. to about 150° C., about 100° C. to about 125° C., about 125° C. to about 250° C., about 125° C. to about 200° C., about 125° C. to about 150° C., about 150° C. to about 250° C., about 150° C. to about 200° C., or about 200° C. to about 250° C. In some embodiments, the temperature of the mixture in (b) is raised to a temperature between about 50° C. to about 150° C.
[0086]
[0089] In some embodiments, in (c), the temperature is from about 2 minutes to about 240 minutes, from about 2 minutes to about 200 minutes, from about 2 minutes to about 100 minutes, from about 2 minutes to about 60 minutes, from about 2 minutes to about 40 minutes, from about 5 minutes to about 240 minutes, from about 5 minutes to about 200 minutes, from about 5 minutes to about 100 minutes, from about 5 minutes to about 60 minutes, from about 5 minutes to about 40 minutes, from about 10 minutes to about 240 minutes, from about 10 minutes to about 200 minutes, from about 10 minutes The reaction time is maintained for about 10 minutes to about 100 minutes, about 10 minutes to about 60 minutes, about 10 minutes to about 40 minutes, about 40 minutes to about 240 minutes, about 40 minutes to about 200 minutes, about 40 minutes to about 100 minutes, about 40 minutes to about 60 minutes, about 60 minutes to about 240 minutes, about 60 minutes to about 200 minutes, about 60 minutes to about 100 minutes, about 100 minutes to about 240 minutes, about 100 minutes to about 200 minutes, or about 200 minutes to about 240 minutes.
[0087]
[0090] In some embodiments, the progress of the reaction is monitored by examining a sample from the mixture using UV-visible spectroscopy. In some embodiments, after adding the nanostructure core in (c), the temperature is changed so that a sample taken from the mixture has a peak absorbance by UV-visible spectroscopy of about 350 nm to about 500 nm, about 350 nm to about 475 nm, about 350 nm to about 450 nm, about 350 nm to about 425 nm, about 350 nm to about 400 nm, about 350 nm to about 375 nm, about 375 nm to about 500 nm, about 375 nm to about 475 nm, or about 375 nm to about 475 nm. m, about 375 nm to about 450 nm, about 375 nm to about 425 nm, about 375 nm to about 400 nm, about 400 nm to about 500 nm, about 400 nm to about 475 nm, about 400 nm to about 450 nm, about 400 nm to about 425 nm, about 425 nm to about 475 nm, about 425 nm to about 450 nm, about 450 nm to about 500 nm, about 450 nm to about 475 nm, or about 475 nm to about 500 nm. In some embodiments, after adding the nanostructure core in (c), this temperature is maintained until a peak absorbance by UV-visible spectroscopy of a sample taken from the mixture is between about 425 nm and about 450 nm.
[0088]
[0091] In some embodiments, additional shells are produced by adding more shell precursors to the reaction mixture and then maintaining the mixture at an elevated temperature. Typically, the additional shell precursor is provided once the reaction of the previous shell is substantially complete (e.g., once at least one of the previous precursors has been depleted or removed from the reaction or no further growth is detected). This addition of more precursor produces additional shells.
[0089]
[0092] In some embodiments, the nanostructures are cooled before adding additional shell precursor to impart an additional shell, hi some embodiments, the nanostructures are maintained at an elevated temperature before adding shell precursor to impart an additional shell.
[0090]
[0093] In some embodiments, the zinc source used in the preparation of the shell layer is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is zinc diethyl, zinc dimethyl, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.
[0091]
[0094] In some embodiments, the selenium source used in the preparation of at least one outer shell layer is an alkyl-substituted selenide urea. In some embodiments, the selenium source is a phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenide urea, and mixtures thereof. In some embodiments, the selenium source is tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, or tri(tert-butyl)phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.
[0092]
[0095] In some embodiments, each outer shell layer is synthesized in the presence of at least one ligand for the nanostructure. The ligand can, for example, increase the miscibility of the nanostructure in a solvent or polymer (allowing the nanostructure to be distributed throughout the composition so that the nanostructure does not aggregate), increase the quantum yield of the nanostructure, and / or preserve the emission of the nanostructure (e.g., when the nanostructure is incorporated into a matrix). After synthesis, any ligands on the nanostructure surface can be replaced with different ligands having other desirable properties. Examples of ligands are disclosed in U.S. Pat. No. 7,572,395, U.S. Pat. No. 8,143,703, U.S. Pat. No. 8,425,803, U.S. Pat. No. 8,563,133, U.S. Pat. No. 8,916,064, U.S. Pat. No. 9,005,480, U.S. Pat. No. 9,139,770, and U.S. Pat. No. 9,169,435, and U.S. Patent Application Publication No. 2008 / 0118755.
[0093]
[0096] Ligands suitable for the synthesis of the outer shell layer are known to those skilled in the art. In some embodiments, the ligand is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is lauric acid.
[0094]
[0097] Once the ZnSe shell has been added to the InP nanostructures to reach a desired thickness and diameter, the nanostructures can be cooled. In some embodiments, the nanostructures are cooled to room temperature. In some embodiments, an organic solvent is added to dilute the reaction mixture containing the nanostructures.
[0095]
[0098] In some embodiments, the organic solvent used to dilute the reaction mixture containing the nanostructures is ethanol, hexane, pentane, toluene, benzene, diethyl ether, acetone, ethyl acetate, dichloromethane (methylene chloride), chloroform, dimethylformamide, N-methylpyrrolidinone, or a combination thereof, hi some embodiments, the organic solvent is toluene.
[0096]
[0099] In some embodiments, the nanostructures are isolated. In some embodiments, the nanostructures are isolated by precipitation with an organic solvent. In some embodiments, the nanostructures are isolated by flocculation with ethanol.
[0097]
[0100] The size of the nanostructures can be measured using techniques known to those of skill in the art, hi some embodiments, the nanostructure size is measured using a TEM. In some embodiments, the average diameter of the nanostructures is between 1 nm and 15 nm, between 1 nm and 10 nm, between 1 nm and 9 nm, between 1 nm and 8 nm, between 1 nm and 7 nm, between 1 nm and 6 nm, between 1 nm and 5 nm, between 5 nm and 15 nm, between 5 nm and 10 nm, between 5 nm and 9 nm, between 5 nm and 8 nm, between 5 nm and 7 nm, between 5 nm and 6 nm, between 6 nm and 15 nm, between 6 nm and 10 nm, between 6 nm and 9 nm, between 6 nm and 8 nm, between 6 nm and 7 nm, between 7 nm and 15 nm, between 7 nm and 10 nm, between 7 nm and 9 nm, between 7 nm and 8 nm, between 8 nm and 15 nm, between 8 nm and 10 nm, between 8 nm and 9 nm, between 9 nm and 15 nm, between 9 nm and 10 nm, or between 10 nm and 15 nm. In some embodiments, the average diameter of the nanostructures is between 6 nm and 7 nm.
[0098] Fabrication of InP cores with ZnSe shells -C method
[0101] In some embodiments, the present invention provides a method for fabricating a core / shell InP / ZnSe nanostructure, comprising: (a) adding InP cores to a solution containing a solvent, a ligand, and zinc chloride under an inert atmosphere at a temperature of about 80° C. to about 320° C.; (b) adding zinc bromide and gallium chloride to the solution obtained in (a); (c) adding a source of selenium to the solution obtained in (b); (d) heating the solution obtained in (c) to a temperature of about 250° C. to about 320° C.; (e) allowing the solution obtained in (d) to cool; The present invention relates to a method comprising the steps of:
[0099]
[0102] In some embodiments, the solution in (a) is heated to a temperature of about 80°C-140°C, 90°C-140°C, 100°C-140°C, 110°C-140°C, 120°C-140°C, 130°C-140°C, 80°C-130°C, 90°C-130°C, 100°C-130°C, 110°C-130°C, 120°C-130°C, 80°C-110°C, 90°C-110°C, 100°C-110°C, or about 100°C.
[0100]
[0103] In some embodiments, the solvent is selected from the group consisting of 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, and dioctyl ether, hi some embodiments, the solvent is 1-octadecene.
[0101]
[0104] In some embodiments, the ligand added in (a) is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is lauric acid.
[0102]
[0105] In some embodiments, the molar ratio of InP QDs to zinc chloride in (a) is in the range of 1:0.5 to 1:4, in other embodiments, the molar ratio of InP QDs to zinc chloride is about 1:1.
[0103]
[0106] In some embodiments, the molar ratio of InP QDs to zinc bromide in (b) ranges from 1:0.5 to 1:4, in other embodiments, the molar ratio of InP QDs to zinc bromide is about 1:0.6.
[0104]
[0107] In some embodiments, the molar ratio of InP QDs to gallium chloride in (b) is in the range of 1:0.5 to 1:4, in other embodiments, the molar ratio of InP QDs to gallium chloride is about 1:0.7.
[0105]
[0108] In some embodiments, the selenium source is an alkyl selenide or selenium powder.
[0106]
[0109] In some embodiments, the temperature in (d) is raised to 200° C. to 300° C. In other embodiments, the temperature of the solution is raised to 210° C. to 300° C., 220° C. to 300° C., 230° C. to 300° C., 240° C. to 300° C., 250° C. to 300° C., 260° C. to 300° C., 270° C. to 300° C., 280° C. to 300° C., 290° C. to 300° C., 210° C. to 290° C., 220° C. to 290° C., 230° C. to 290° C., 240° C. to 290° C., 250° C. to 290° C., 260° C. to 290° C., 270° C. to 290° C., 280° C. to 290° C. The temperature is raised to 210°C to 280°C, 220°C to 280°C, 230°C to 280°C, 240°C to 280°C, 250°C to 280°C, 260°C to 280°C, 270°C to 280°C, 210°C to 270°C, 220°C to 270°C, 230°C to 270°C, 240°C to 270°C, 250°C to 270°C, 260°C to 270°C, 210°C to 260°C, 220°C to 260°C, 230°C to 260°C, 240°C to 260°C, or about 250°C. The raised temperature is maintained for about 5 minutes to about 5 hours. In other embodiments, the elevated temperature is held for 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 280, 290, 300, or about 120 minutes.
[0107] Nanostructure properties
[0110] In some embodiments, the nanostructures exhibit high photoluminescence quantum yields, such as from about 60% to about 99%, from about 60% to about 95%, from about 60% to about 90%, from about 60% to about 85%, from about 60% to about 80%, from about 60% to about 70%, from about 70% to about 99%, from about 70% to about 95%, from about 70% to about 90%, from about 70% to about 85%, from about 70% to about 80%, from about 80% to about 99%, about 80% to about 95%, about 80% to about 90%, about 80% to about 85%, about 85% to about 99%, about 85% to about 95%, about 80% to about 85%, about 85% to about 99%, about 85% to about 95%, about 80% to about 85%, about 85% to about 99%, about 85% to about 90%, about 90% to about 99%, about 90% to about 95%, or about 95% to about 99%. In some embodiments, the nanostructure exhibits a photoluminescence quantum yield of between about 85% to about 90%. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0108]
[0111] The photoluminescence spectrum of the nanostructure can span essentially any desired portion of the spectrum. In some embodiments, the photoluminescence spectrum of the nanostructure has an emission maximum between 300 nm and 750 nm, 300 nm and 650 nm, 300 nm and 550 nm, 300 nm and 450 nm, 450 nm and 750 nm, 450 nm and 650 nm, 450 nm and 550 nm, 450 nm and 750 nm, 450 nm and 650 nm, 450 nm and 550 nm, 550 nm and 750 nm, 550 nm and 650 nm, or 650 nm and 750 nm. In some embodiments, the photoluminescence spectrum of the nanostructure has an emission maximum between 450 nm and 550 nm. In some embodiments, the photoluminescence spectrum of the nanostructure has an emission maximum between 530 nm and 540 nm. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0109]
[0112] The particle size distribution of the nanostructures can be relatively narrow. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the population of nanostructures can be between 10 nm to 60 nm, 10 nm to 40 nm, 10 nm to 30 nm, 10 nm to 20 nm, 20 nm to 60 nm, 20 nm to 40 nm, 20 nm to 30 nm, 30 nm to 60 nm, 30 nm to 40 nm, or 40 nm to 60 nm. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the population of nanostructures can be between 35 nm to 50 nm. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0110] Surface treatment of nanostructures
[0113] The nanostructures are subjected to a surface treatment that unexpectedly improves EQE and lifetime when used in a device. The surface treatment comprises treatment at elevated temperature with a solution containing a zinc carboxylate and a zinc halide under an inert atmosphere. In some embodiments, the zinc carboxylate is zinc acetate. In some embodiments, the zinc halide is zinc fluoride. In one embodiment, the zinc acetate is in the form of a dihydrate. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0111]
[0114] The molar ratio of zinc acetate to zinc fluoride can range from 1 to 5. In some embodiments, the molar ratio of zinc acetate to zinc fluoride can range from 2 to 5, 3 to 5, 4 to 5, 2 to 4, 3 to 5, 4 to 5, 2 to 4, or 2 to 3. In one embodiment, the molar ratio of zinc acetate to zinc fluoride is about 2:3. In one embodiment, the molar ratio of zinc acetate to InP core is 4:1 to 35:1. In another embodiment, the molar ratio of zinc fluoride to InP core is 1:9 to 1:40. In another embodiment, the molar ratio of zinc acetate, zinc fluoride, and InP core is about 20:28:1.
[0112]
[0115] In some embodiments, zinc acetate dihydrate and zinc fluoride are added to the solution containing the InP nanocrystals. The addition temperature can be in the range of 0°C to 100°C. In another embodiment, the temperature of the solution at the time of addition is 10°C to 100°C, 20°C to 100°C, 30°C to 100°C, 40°C to 100°C, 50°C to 100°C, 60°C to 100°C, 70°C to 100°C, 80°C to 100°C, 90°C to 100°C, 0°C to 90°C, 10°C to 90°C, 20°C to 90°C, 30°C to 90°C, 40°C to 90°C, 50°C to 90°C, 60°C to 90°C, 70°C to 90°C, 80°C to 90°C, 0°C to 80°C, 10°C to 80°C, 20°C to 80°C, 30°C to 80°C, 40°C to 80°C, 50°C to 80°C, 60°C to 80°C, 70°C to 8 ...80°C, 80°C to 80°C, 80°C to 80°C, 80°C to 80°C, 80°C to 80°C, 80°C to 80° The temperature may be in the range of ℃ to 80℃, 0℃ to 70℃, 10℃ to 70℃, 20℃ to 70℃, 30℃ to 70℃, 40℃ to 70℃, 50℃ to 70℃, 60℃ to 70℃, 0℃ to 60℃, 10℃ to 60℃, 20℃ to 60℃, 30℃ to 60℃, 40℃ to 60℃, 50℃ to 60℃, 0℃ to 50℃, 10℃ to 50℃, 20℃ to 50℃, 30℃ to 50℃, 40℃ to 50℃, 0℃ to 40℃, 10℃ to 40℃, 20℃ to 40℃, 30℃ to 40℃, 0℃ to 30℃, 10℃ to 30℃, 20℃ to 30℃, 0℃ to 20℃, 10℃ to 20℃ or room temperature.
[0113]
[0116] Then, the reaction temperature is raised to 200° C. to 300° C. In another embodiment, the temperature of the solution is 210° C. to 300° C., 220° C. to 300° C., 230° C. to 300° C., 240° C. to 300° C., 250° C. to 300° C., 260° C. to 300° C., 270° C. to 300° C., 280° C. to 300° C., 290° C. to 300° C., 200° C. to 290° C., 210° C. to 290° C., 220° C. to 290° C., 230° C. to 290° C., 240° C. to 290° C., 250° C. to 290° C., 260° C. to 290° C., 270° C. to 290° C., 280° C. to 290° C., 200° C. to 280° C., 210° C. to 280° C., 220° C. to 280° C., 230° C. to 280° C. °C, 240°C to 280°C, 250°C to 280°C, 260°C to 280°C, 270°C to 280°C, 200°C to 270°C, 210°C to 270°C, 220°C to 270°C, 230°C to 270°C, 240°C to 270°C, 250°C to 270°C, 260°C to 270°C, 200°C to 260°C, 210°C to 260°C, 220°C to 260°C, 230°C to 260°C, 240°C to 260°C, 250°C to 260°C, 200°C to 250°C, 210°C to 250°C, 220°C to 250°C, 230°C to 250°C, 240°C to 250°C, or about 250°C. The elevated temperature is maintained for 1 to 5 hours, hi other embodiments, the elevated temperature is maintained for 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 280, 290, 300, or about 120 minutes.
[0114]
[0117] The reaction is then allowed to cool to 50°C to 150°C. In other embodiments, the reaction mixture is allowed to cool to 50°C to 140°C, 60°C to 140°C, 70°C to 140°C, 80°C to 140°C, 90°C to 140°C, 100°C to 140°C, 110°C to 140°C, 120°C to 140°C, 130°C to 140°C, 50°C to 130°C, 60°C to 130°C, 70°C to 130°C, 80°C to 130°C, 90°C to 130°C, 100°C to 130°C, 110°C to 130°C, 120°C to 130°C, 50°C to 120°C, 60°C to 120°C, 70°C to 120°C, 80°C to 120°C, 90°C to 120°C, 100°C to 120°C, 110°C to 120°C, or about 100°C.
[0115]
[0118] After cooling the reaction, the ligand is added. In some embodiments, TOP is added. The core-shell nanostructures having zinc acetate and zinc fluoride on their surface can then be isolated by any method known for isolating nanostructures. In one embodiment, the core-shell nanostructures are isolated by precipitation and / or centrifugation and washed with a solvent. In one embodiment, the core-shell nanostructures are precipitated by adding an alcohol, such as ethanol, and hexane. In one embodiment, the core-shell nanostructures are InP / ZnSe.
[0116] Peak Emission Wavelength
[0119] In some embodiments, the core-shell nanostructure emits light having a peak emission wavelength (PWL) between about 400 nm to about 650 nm, about 400 nm to about 600 nm, about 400 nm to about 550 nm, about 400 nm to about 500 nm, about 400 nm to about 450 nm, about 450 nm to about 650 nm, about 450 nm to about 600 nm, about 450 nm to about 550 nm, about 450 nm to about 500 nm, about 500 nm to about 650 nm, about 500 nm to about 600 nm, about 500 nm to about 550 nm, about 550 nm to about 650 nm, about 550 nm to about 600 nm, or about 600 nm to about 650 nm. In some embodiments, the nanostructure emits light having a PWL between about 500 nm to about 550 nm. In some embodiments, the nanostructure emits light with a PWL between about 530 nm and about 540 nm, hi one embodiment, the core-shell nanostructure is InP / ZnSe.
[0117] Films, Devices, and Uses
[0120] The population of core-shell nanostructures can optionally be embedded in a matrix (e.g., organic polymer, silicon-containing polymer, inorganic, glassy, and / or other matrix) to form a film. The film can be used to manufacture nanostructured phosphors and / or can be incorporated into devices such as LEDs, backlights, downlights, or other display or lighting units or optical filters. Exemplary phosphors and lighting units can, for example, incorporate a population of nanostructures with an emission maximum at or near a desired wavelength to produce a specific color of light, or incorporate two or more different populations of nanostructures with different emission maxima to produce a wide color gamut. A variety of suitable matrices are known in the art. See, for example, U.S. Pat. No. 7,068,898 and U.S. Pat. App. Pub. Nos. 2010 / 0276638, 2007 / 0034833, and 2012 / 0113672. Exemplary nanostructured phosphorescent films, LEDs, backlight units, and the like are described, for example, in U.S. Patent Application Publication Nos. 2010 / 0276638, 2012 / 0113672, 2008 / 0237540, 2010 / 0110728, and 2010 / 0155749, as well as U.S. Patent Nos. 7,374,807, 7,645,397, 6,501,091, and 6,803,719. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0118]
[0121] In some embodiments, the nanostructure films are used to form display devices. As used herein, a display device refers to any system having an illuminated display. Such devices include, but are not limited to, devices that contain liquid crystal displays (LCDs), televisions, computers, mobile phones, smart phones, personal digital assistants (PDAs), gaming devices, electronic reading devices, digital cameras, and the like.
[0119]
[0122] In some embodiments, the present disclosure provides a nanostructure molded article comprising: (a) a first conductive layer; (b) a second conductive layer; (c) a nanostructure layer between the first conductive layer and the second conductive layer; wherein the nanostructure layer comprises a population of nanostructures comprising a nanocrystalline core and at least one shell having zinc acetate and zinc fluoride bound to a surface thereof, hi some embodiments, the core-shell nanostructures are InP / ZnSe.
[0120]
[0123] In some embodiments, the present disclosure provides a nanostructure film comprising: (a) a population of at least one nanostructure, the nanostructure comprising a core and at least one shell having a zinc carboxylate and a zinc halide bound to a surface thereof; (b) at least one organic resin; The present invention provides a nanostructure film comprising:
[0121]
[0124] In some embodiments, the core-shell nanostructure is InP / ZnSe.
[0122]
[0125] In some embodiments, the core / shell nanostructures are embedded in the matrix. As used herein, the term "embedded" is used to denote that the nanostructures are enclosed or encased in the matrix material that constitutes the majority of the matrix's constituent elements. In some embodiments, the nanostructures are uniformly distributed throughout the matrix material. In some embodiments, the nanostructures are distributed according to an application-specific uniform distribution function.
[0123]
[0126] The matrix material can be any suitable host matrix material capable of housing the nanostructures. Suitable matrix materials can be chemically and optically compatible with the surrounding packaging materials or layers used in applying the nanostructures and nanostructure films to the device. Suitable matrix materials can include non-yellowing optical materials that are transparent to both primary and secondary light, thereby allowing the primary and secondary light to be transmitted through the matrix material. Matrix materials can include polymers and organic and inorganic oxides. Suitable polymers for use in the matrix material can be any polymer known to those skilled in the art that can be used for this type of purpose. The polymer can be substantially translucent or substantially transparent. Matrix materials can include, but are not limited to, epoxies, acrylates, norbornenes, polyethylene, poly(vinyl butyral), poly(vinyl acetate), polyureas, polyurethanes, silicones and silicone derivatives, including, but not limited to, aminosilicones (AMS), polyphenylmethylsiloxanes, polyphenylalkylsiloxanes, polydiphenylsiloxanes, polydialkylsiloxanes, silsesquioxanes, fluorosilicones, vinyl and hydride substituted silicones; acrylic polymers and copolymers formed from monomers such as, but not limited to, methyl methacrylate, butyl methacrylate, and lauryl methacrylate; styrenic polymers such as polystyrene, aminopolystyrene (APS), and poly(acrylonitrile ethylene styrene) (AES); polymers crosslinked with difunctional monomers such as divinylbenzene; crosslinkers suitable for crosslinking ligand materials, epoxides that combine with amine ligands (e.g., amine ligands APS or polyethyleneimine) to form epoxies, and the like.
[0124]
[0127] In some embodiments, the matrix material can enhance the light conversion efficiency of the nanostructure film, such as TiO 2microbeads, ZnS microbeads, or glass microbeads, etc. In some embodiments, the matrix material can include light blocking elements.
[0125]
[0128] In some embodiments, the matrix material can have low oxygen and moisture permeability, exhibit light and chemical stability, exhibit a favorable refractive index, and adhere to the exterior surfaces of the nanostructures, thereby providing a hermetic encapsulant to protect the nanostructures, hi other embodiments, the matrix material can be curable by UV or thermal curing methods to facilitate roll-to-roll processing.
[0126]
[0129] In some embodiments, nanostructure films can be formed by mixing the nanostructures in a polymer (e.g., photoresist) and casting the nanostructure-polymer mixture onto a substrate, by mixing the nanostructures with a monomer and polymerizing them together, by mixing the nanostructures in a sol-gel to form an oxide, or by any other method known to one of skill in the art.
[0127]
[0130] In some embodiments, forming the nanostructure film can include a film extrusion process. The film extrusion process can include forming a homogenous mixture of the matrix material and the core-shell nanostructures and introducing the homogenous mixture into a top-mounted hopper that feeds the extruder. In some embodiments, the homogenous mixture can be in pellet form. The film extrusion process can further include extruding the nanostructure film from a slot die and passing the extruded nanostructure film through a chill roll. In some embodiments, the thickness of the extruded nanostructure film can be less than about 75 μm, such as from about 70 μm to about 40 μm, from about 65 μm to about 40 μm, from about 60 μm to about 40 μm, or from about 50 μm to about 40 μm. In some embodiments, the thickness of the nanostructure film is less than about 10 μm. In some embodiments, forming the nanostructure film can optionally include a second process following the film extrusion process. This second process can include processes such as coextrusion, thermoforming, vacuum forming, plasma treating, molding, and / or embossing to impart texture to the top surface of the nanostructure film layer. Imparting texture to the top surface of the nanostructure film can help improve, for example, the defined optical diffusion properties and / or defined angular optical emission properties of the nanostructure film.
[0128]
[0131] In some embodiments, the nanostructure composition is used to form a nanostructure article. In some embodiments, the nanostructure article is a liquid crystal display (LCD) or a light emitting diode (LED). In some embodiments, the nanostructure composition is used to form a light emitting layer of a lighting device. The lighting device can be used in a wide range of applications, such as flexible electronics, touch screens, monitors, televisions, mobile phones, and any other high resolution displays. In some embodiments, the lighting device is a light emitting diode or a liquid crystal display. In some embodiments, the lighting device is a quantum dot light emitting diode (QLED). Examples of QLEDs are described in U.S. Patent Application Publication No. 15 / 824,701, the entire disclosure of which is incorporated herein by reference. In some embodiments, the core-shell nanostructure is InP / ZnSe.
[0129]
[0132] In some embodiments, the present disclosure provides a light emitting diode comprising: (a) a first conductive layer; (b) a second conductive layer; (c) a light emitting layer between the first conductive layer and the second conductive layer; wherein the light emitting layer includes a population of at least one nanostructure comprising: (i) a nanocrystalline core having zinc acetate and zinc fluoride bound to a surface thereof.
[0130]
[0133] In some embodiments, the core-shell nanostructure is InP / ZnSe.
[0131]
[0134] In some embodiments, the light-emitting layer is a nanostructured film.
[0132]
[0135] In some embodiments, the light emitting diode comprises a first conductive layer, a second conductive layer, and a light emitting layer, the light emitting layer being disposed between the first conductive layer and the second conductive layer, hi some embodiments, the light emitting layer is a thin film.
[0133]
[0136] In some embodiments, the light emitting diode comprises additional layers between the first conductive layer and the second conductive layer, such as a hole injection layer, a hole transport layer, and an electron transport layer. In some embodiments, the hole injection layer, the hole transport layer, and the electron transport layer are thin films. In some embodiments, the layers are laminated onto a substrate.
[0134]
[0137] When a voltage is applied to the first and second conductive layers, holes injected into the first conductive layer migrate through the hole injection layer and / or hole transport layer to the light-emitting layer, and electrons injected from the second conductive layer migrate through the electron transport layer to the light-emitting layer. The holes and electrons recombine in the light-emitting layer to generate excitons. In some embodiments, the hole transport layer comprises poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] (TFB).
[0135]
[0138] In some embodiments, the nanostructure film is incorporated into a quantum dot on glass LCD display device. The LCD display device may include a nanostructure film formed directly on a light guide plate (LGP) without the need for an intermediate substrate or barrier layer. In some embodiments, the nanostructure film may be a thin film. In some embodiments, the nanostructure film may have a thickness of 500 μm or less, 100 μm or less, or 50 μm or less. In some embodiments, the nanostructure film is a thin film having a thickness of about 15 μm or less. In some embodiments, the core-shell nanostructure is InP / ZnSe.
[0136]
[0139] The LGP may include an optical cavity comprising glass having one or more surfaces, including at least a top surface. Glass provides a high resistance to impurities, including moisture and air. Additionally, glass may be formed as a thin substrate that maintains structural integrity. Thus, the LGP may be formed at least in part on a glass surface to provide a substrate with sufficient barrier and structural properties.
[0137]
[0140] In some embodiments, a nanostructure film can be formed on the LGP. In some embodiments, the nanostructure film includes a population of nanostructures embedded in a matrix material, such as a resin. The nanostructure film can be formed on the LGP by any method known in the art, such as wet coating, painting, spin coating, or screen printing. After the nanostructure film is deposited, the resin can be cured. In some embodiments, the resin of one or more nanostructure films can be partially cured and further processed before final curing. The nanostructure film can be deposited as a layer or as separate layers, and the separate layers can have different properties. The width and height of the nanostructure film can have any desired dimensions depending on the size of the viewing panel of the display device. For example, the nanostructure film can have a relatively small surface area for small display device embodiments such as watches and phones, or the nanostructure film can have a large surface area for large display device embodiments such as TVs and computer monitors.
[0138]
[0141] In some embodiments, an optically transparent substrate is formed on the nanostructure film by any method known in the art, such as vacuum deposition, vapor deposition, or the like. The optically transparent substrate can be configured to environmentally seal the underlying layers and / or structures of the nanostructure film. In some embodiments, a light blocking element can be included in the optically transparent substrate. In some embodiments, the light blocking element can be included in a second polarizing filter disposed between the substrate and the nanostructure film. In some embodiments, the light blocking element can be, for example, a dichroic filter that can transmit a second light while reflecting a first light (e.g., blue light, UV light, or a combination of UV light and blue light). The light blocking element can include a specific UV light blocking component to remove unconverted UV light from the red and green subpixels and / or to remove UV light from the blue subpixels.
[0139]
[0142] In some embodiments, the nanostructures are incorporated into the display device in an "on-chip" configuration. As used herein, "on-chip" refers to disposing the nanostructures within the LED cup. In some embodiments, the nanostructures are dissolved in a resin or fluid to fill the LED cup.
[0140]
[0143] In some embodiments, the nanostructures are incorporated into the display device in a "near-chip" configuration, which as used herein refers to coating the nanostructures on the top surface of an LED assembly such that the emitted light passes through the nanostructure film.
[0141]
[0144] In some embodiments, the present invention provides a display device comprising: (a) a first light-emitting display panel; (b) a backlight unit configured to provide a first light to the display panel; (c) a color filter including at least one pixel region having a color conversion layer; A display device is provided, comprising:
[0142]
[0145] In some embodiments, the color filter has at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 pixel regions. In some embodiments, when blue light is incident on the color filter, red light, white light, green light, and / or blue light can be emitted through the pixel regions, respectively. In some embodiments, the color filter is described in U.S. Patent Application No. 2017 / 153366, which is incorporated herein by reference in its entirety.
[0143]
[0146] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to a first color of light. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to blue light.
[0144]
[0147] In some embodiments, the display device comprises 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 color conversion layers. In some embodiments, the display device comprises one color conversion layer comprising the nanostructures described herein. In some embodiments, the display device comprises two color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises three color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises four color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises at least one red conversion layer, at least one green conversion layer, and at least one blue conversion layer.
[0145]
[0148] In some embodiments, the thickness of the color conversion layer is between about 3 μm and about 10 μm, about 3 μm and about 8 μm, about 3 μm and about 6 μm, about 6 μm and about 10 μm, about 6 μm and about 8 μm, or about 8 μm and about 10 μm. In some embodiments, the thickness of the color conversion layer is between about 3 μm and about 10 μm.
[0146]
[0149] The color conversion layer of the nanostructures can be deposited by any suitable method known in the art, including, but not limited to, painting, spray coating, solvent spraying, wet coating, adhesive coating, spin coating, tape-coating, roll coating, flood coating, inkjet printing, photoresist patterning, drop casting, blade coating, mist deposition, or combinations thereof. In some embodiments, the color conversion layer of the nanostructures is deposited by photoresist patterning. In some embodiments, the color conversion layer of the nanostructures is deposited by inkjet printing.
[0147]
[0150] Core-shell nanostructures can be used for imaging or labeling, for example, biological imaging or biological labeling. The resulting nanostructures are thus optionally covalently or non-covalently attached to biomolecules, such as, but not limited to, peptides or proteins (e.g., antibodies or antibody regions, avidin, streptavidin, neutravidin, or other binding or recognition molecules), ligands (e.g., biotin), polynucleotides (e.g., short oligonucleotides or longer nucleic acids), carbohydrates, lipids (e.g., phospholipids or other micelles). One or more nanostructures can be attached to each biomolecule as desired for a given application. Biomolecules labeled with this type of nanostructure find use, for example, in investigating binding or chemical reactions, as well as in cellular components, cells, and biolabeling, for example, in vitro, in vivo, and in cellulo. In one embodiment, the core-shell nanostructure is InP / ZnSe.
[0148]
[0151] Core-shell nanostructures obtained by this method are also a feature of the invention. Thus, one class of embodiments provides a population of core-shell nanostructures. In some embodiments, the nanostructures are quantum dots. In one embodiment, the core-shell nanostructures are InP / ZnSe.
[0149] Inkjet printing
[0152] The formation of thin films using dispersions of nanostructures in organic solvents is often accomplished using coating techniques such as spin-coating. However, these coating techniques are generally not suitable for forming large-area thin films and do not provide a means for patterning the deposited layers, and therefore have limited use. Inkjet printing allows for precise patterning of thin films at large scale and low cost. Inkjet printing can also precisely pattern nanostructure layers, allowing for the printing of display pixels without the need for photopatterning. Inkjet printing is therefore very attractive for industrial applications, particularly for displays.
[0150]
[0153] Commonly used solvents for inkjet printing are dipropylene glycol monomethyl ether acetate (DPMA), polyglycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC), and propylene glycol methyl ether acetate (PGMEA). Volatile solvents are also commonly used for inkjet printing because they dry quickly. Volatile solvents include ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, and tetrahydrofuran. Conventional nanostructures generally cannot be dissolved in these solvents. However, nanostructures containing poly(alkylene oxide) ligands have increased hydrophilicity, which can increase their solubility in these solvents.
[0151]
[0154] In some embodiments, the nanostructures described herein used for inkjet printing are dispersed in a solvent selected from DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, chloroform, chlorobenzene, cyclohexane, hexane, heptane, octane, hexadecane, undecane, decane, dodecane, xylene, toluene, benzene, octadecane, tetradecane, butyl ether, or combinations thereof. In some embodiments, the nanostructures comprising the poly(alkylene oxide) ligands described herein used for inkjet printing are dispersed in a solvent selected from DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, or combinations thereof.
[0152]
[0155] For inkjet printing or microdispensing applications, the inkjet composition containing the nanostructures needs to be dissolved in a suitable solvent, which must be capable of dispersing the nanostructure composition and must not adversely affect the print head selected.
[0153]
[0156] In some embodiments, the inkjet composition further comprises one or more additional components, such as surface active compounds, lubricants, wetting agents, dispersants, hydrophobizing agents, adhesives, flow improvers, defoamers, degassing agents, diluents, adjuvants, colorants, dyes, pigments, sensitizers, stabilizers, and inhibitors.
[0154]
[0157] In some embodiments, the nanostructure compositions described herein comprise from about 0.01% to about 20% by weight of the ink-jet composition. In some embodiments, the nanostructures comprising poly(alkylene oxide) ligands are present in an amount by weight of the inkjet composition of from about 0.01% to about 20%, from about 0.01% to about 15%, from about 0.01% to about 10%, from about 0.01% to about 5%, from about 0.01% to about 2%, from about 0.01% to about 1%, from about 0.01% to about 0.1%, from about 0.01% to about 0.05%, from about 0.05% to about 20%, from about 0.05% to about 15%, from about 0.05% to about 10%, from about 0.05% to about 5%, from about 0.05% to about 2%, from about 0.05% to about 1%, from about 0.05% to about 0.1%, from about 0.1% to about 20%, from about 0.1% to about 20%, About 15%, about 0.1% to about 10%, about 0.1% to about 5%, about 0.1% to about 2%, about 0.1% to about 1%, about 0.5% to about 20%, about 0.5% to about 15%, about 0.5% to about 10%, about 0.5% to about 5%, about 0.5% to about 2%, about 0.5% to about 1%, about 1% to about 20%, about 1% to about 15 %, about 1% to about 10%, about 1% to about 5%, about 1% to about 2%, about 2% to about 20%, about 2% to about 15%, about 2% to about 10%, about 2% to about 5%, about 5% to about 20%, about 5% to about 15%, about 5% to about 10%, about 10% to about 20%, about 10% to about 15%, or about 15% to 20%.
[0155]
[0158] In some embodiments, the inkjet composition comprising the nanostructures or nanostructure compositions described herein is used to form an electronic device. In some embodiments, the inkjet composition of the nanostructures or nanostructure compositions described herein is used to form an electronic device selected from the group consisting of nanostructure films, display devices, lighting devices, backlight units, color filters, surface emitting devices, electrodes, magnetic storage devices, and batteries. In some embodiments, the inkjet composition comprising the nanostructure compositions described herein is used to form a light emitting device. EXAMPLES
[0156]
[0159] The following examples are illustrative, but not limiting, of the products and methods described herein. Suitable modifications and adaptations of the variety of conditions, formulations, and other parameters normally encountered in this field and obvious to those skilled in the art in light of this disclosure are within the spirit and scope of the invention.
[0157] Example 1 Fabrication of InP / ZnSe green light-emitting nanostructures
[0160] InP / ZnSe green light-emitting nanostructures were fabricated using the process described below.
[0158]
[0161] Weigh out 28.2895 grams of zinc oleate and 8.0631 grams of lauric acid.
[0159]
[0162] The zinc oleate and lauric acid are added to a 3-neck round bottom flask, and 79.65 mL of 1-octadecene (ODE) and a stir bar are added to the flask.
[0160]
[0163] A rubber septum, a thermocouple adapter with a thermocouple, and a Schlenk adapter are attached to the flask and the flask is connected to a Schlenk line.
[0161]
[0164] The solution is carefully degassed with vigorous stirring at room temperature.
[0162]
[0165] The flask is placed under a stream of nitrogen from a Schlenk line.
[0163]
[0166] The flask is lowered into a heating mantle and the solution is heated to approximately 90° C. under a stream of nitrogen.
[0164]
[0167] Once a clear, colorless solution is obtained, the flask is carefully evacuated for several minutes with vigorous stirring.
[0165]
[0168] The flask is placed under a stream of nitrogen and the solution is heated to 110°C.
[0166]
[0169] Once the solution has reached 110° C., add 150 mg of zinc chloride, which has been weighed into a vial in the glove box.
[0167]
[0170] Once the temperature of the solution has stabilized at 110 °C, add 4.13 mL of InP core (150 mg, equivalent to 1.02 mmol of InP core) and etch the core with the solution for 10 min.
[0168]
[0171] After 10 minutes, the rubber septum was removed and the weighed ZnBr 2 150mg and GaCl 3 Quickly add 300 mg and immediately replace the rubber septum.
[0169]
[0172] 1.73 mL of 1.92 M TOPSe in TOP is injected through the rubber septum and the solution is heated to 270°C.
[0170]
[0173] As soon as the temperature reaches 270° C., 325.94 mg of Se powder is pumped together with 20 ml of ODE using a syringe pump.
[0171]
[0174] The temperature is raised to 310° C. and held at this temperature for 20 minutes.
[0172]
[0175] After 20 minutes, turn off the heat from the temperature controller, remove the heating mantle under the flask, and allow the flask to cool.
[0173] Example 2 Surface treatment of InP / ZnSe green-emitting nanostructures
[0176] After the reaction mixture from Example 1 was cooled to room temperature, the rubber septum was quickly removed and 4.36 grams of zinc acetate dihydrate and 3 grams of zinc fluoride were added to the flask. The rubber septum was quickly replaced.
[0174]
[0177] The flask was placed back into the heating mantle and heated to 250° C. This temperature was held for 2 hours.
[0175]
[0178] After 2 hours, the flask was allowed to cool to 100°C.
[0176]
[0179] After the flask had cooled to approximately 100° C., 34 mL of TOP, which had been prepared in the glove box, was added via syringe.
[0177]
[0180] The flask was then carefully evacuated, the flask was sealed with a Schlenk adapter, and the flask was transferred to a glove box along with several Teflon bottles.
[0178]
[0181] The undissolved material was precipitated by centrifugation at 5000 rpm for 30 min at room temperature. Hexane and EtOH were added to the clear solution, and the suspension was centrifuged at 4000 rpm for 15 min. This was repeated three times to obtain purified surface-treated InP / ZnSe nanostructures.
[0179] Example 3 Characterization of surface-treated InP / ZnSe green-emitting nanostructures
[0182] QLED devices were fabricated to test the surface-treated core / shell nanostructures. The devices consisted of an ITO-coated glass substrate, a PEDOT-PSS-containing hole injection layer (HIL), a hole transport layer, a nanostructured layer in anhydrous octane, an ETL layer (ZnMgO), and a cathode layer (aluminum). Table 1 shows the test results for devices containing InP / ZnSe / ZnS, InP / ZnSe, and InP / ZnSe in the nanostructured layer using surface treatment condition 1, and devices containing InP / ZnSe using surface treatment condition 2.
[0180] [Table 1]
[0181]
[0183] As can be seen from Table 1, the QY and FWHM of the InP / ZnSe core-shell nanostructures were 58.5% and 53.8 nm, which were lower than the 90.8% and 36.4 nm observed for the InP / ZnSe / ZnS core-shell nanostructures, respectively. However, when the InP / ZnSe core-shell nanostructures were surface-treated with zinc acetate dihydrate and zinc fluoride for 2 hours, the QY recovered to 85.1% and the FWHM narrowed to 37.9 nm. Extending the surface treatment to 10 hours (treatment condition 2) increased the QY to 88.2% and narrowed the FWHM to 39.3 nm.
[0182]
[0184] While various embodiments have been described above, it should be understood that they have been presented for illustrative purposes only, and are not limiting. It will be apparent to those skilled in the relevant art that various changes in form and detail can be made therein without departing from the spirit and scope of the present invention. Thus, the breadth and scope should not be limited by any of the above-described exemplary embodiments, but should be defined only in accordance with the following claims and their equivalents.
[0183]
[0185] All patents and patent applications mentioned in this specification are indicative of the level of skill of those skilled in the art to which this invention pertains, and are hereby incorporated by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually incorporated by reference herein.
Claims
1. a nanocrystalline core and at least one shell having a zinc carboxylate and a zinc halide bound to a surface thereof; the nanocrystalline core comprises InP or CdSe; said at least one shell is ZnSe; A collection of nanostructures.
2. The population of nanostructures of claim 1 , wherein the at least one shell has a thickness of between 0.9 nm and 1.1 nm.
3. The population of nanostructures of claim 1 or 2, wherein the nanostructures have diameters between 3.6 nm and 13.2 nm.
4. The population of nanostructures of any one of claims 1 to 3, which are InP / ZnSe core-shell nanostructures.
5. The population of nanostructures of any one of claims 1 to 3, which are CdSe / ZnSe core-shell nanostructures.
6. The population of nanostructures of any one of claims 1 to 5, wherein the full width at half maximum (FWHM) of the emission spectrum is less than 40 nm.
7. The population of nanostructures of any one of claims 1 to 6, wherein the FWHM of the emission spectrum is 38-39 nm.
8. The population of nanostructures of any one of claims 1 to 7, having a quantum yield (QY%) of greater than 80%.
9. The population of nanostructures of any one of claims 1 to 8, wherein QY% is 85-88%.
10. The population of nanostructures of any one of claims 1 to 9, wherein the zinc carboxylate is zinc acetate.
11. 11. The population of nanostructures of claim 10, wherein the zinc carboxylate is zinc acetate dihydrate.
12. The population of nanostructures of any one of claims 1 to 11, wherein the zinc halide is zinc fluoride.
13. A method for producing a population of nanostructures according to any one of claims 1 to 12, comprising the steps of: (a) combining a population of core-shell nanostructures in a solvent with a zinc carboxylate and a zinc halide under an inert atmosphere; (b) increasing the temperature of the mixture of (a) to a temperature between 81° C. and 385° C.; (c) isolating a population of core-shell nanostructures having a zinc carboxylate and a zinc halide bound to their surfaces; The method includes:
14. 14. The method of claim 13, wherein the solvent comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, or dioctyl ether, or a combination thereof.
15. The method of claim 13 or 14, wherein the solvent comprises 1-octadecene.
16. The method according to any one of claims 13 to 15, wherein the mixing in (a) is carried out at a temperature between 0°C and 165°C.
17. The method of any one of claims 13 to 16, wherein the population of nanostructures is a population of InP / ZnSe core-shell nanostructures.
18. The method according to any one of claims 13 to 17, wherein the zinc carboxylate is zinc acetate.
19. 20. The method of claim 18, wherein the zinc acetate is in the form of zinc acetate dihydrate.
20. The population of core-shell nanostructures comprises: (d) adding the InP cores to a solution containing a solvent, a ligand, and zinc chloride under an inert atmosphere at a temperature between 72° C. and 165° C.; (e) adding zinc bromide and gallium chloride to the solution obtained in (d); (f) adding a source of selenium to the solution obtained in (e); (g) heating the solution obtained in (f) to a temperature of from 135° C. to 374° C.; (h) allowing the solution obtained in (g) to cool; The method of claim 13, wherein the compound is obtained by
21. 21. The method of claim 20, wherein the solvent in (d) comprises 1-octadecene, 1-hexadecene, 1-eicosene, eicosane, octadecane, hexadecane, tetradecane, squalene, squalane, trioctylphosphine oxide, trioctylamine, trioctylphosphine, or dioctyl ether, or a combination thereof.
22. The method of claim 20 or 21, wherein the solvent in (d) comprises 1-octadecene.
23. The method of any one of claims 20 to 22, wherein the ligand is a fatty acid.
24. 24. The method of claim 23, wherein the fatty acid is lauric acid.
25. 1. A nanostructure film comprising: (a) at least one population of nanostructures according to any one of claims 1 to 12; (b) at least one organic resin; The nanostructure film comprises:
26. 26. The nanostructure film of claim 25, wherein the nanostructures are embedded in a matrix forming the nanostructure film.
27. 1. A nanostructured article comprising: (a) a first conductive layer; (b) a second conductive layer; (c) a nanostructured layer between the first conductive layer and the second conductive layer; A nanostructure molded article comprising: a nanostructure layer comprising a population of nanostructures according to any one of claims 1 to 12.
28. A display device comprising a population of nanostructures according to any one of claims 1 to 12.
29. 29. A display device according to claim 28, comprising a film comprising a population of nanostructures according to any one of claims 1 to 12.
30. 30. The display device of claim 29, wherein the population of nanostructures is embedded in a matrix forming the film.
31. 31. The display device of claim 29 or 30, wherein the film is disposed on a light guide plate.
Citation Information
Patent Citations
ZnOS / ZnO nanocrystalline and preparation method thereof and illumination device
CN109628082A
Nanocrystal particles and processes for synthesizing the same
US20150083969A1
Quantum dot aggregate particles, production methods thereof, and compositions and electronic devices including the same
US20180044586A1
Multicolor display apparatus
US20180348577A1
Semiconducting light emitting nanoparticle
WO2018178137A1